2006
DOI: 10.1677/joe.1.06278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper and thiomolybdates on bovine theca cell differentiation in vitro

Abstract: Subfertility that will respond to appropriate copper supplementation is a widespread problem in the national dairy herd. The aims of this study were to determine the effect of copper and/or copper chelating thiomolybdates on LH-induced differentiation by looking at the effects on androgen production, steroidogenic enzymes (cytochrome P450 17 -hydroxylase and cytochrome P450 side-chain cleavage) and lysyl oxidase mRNA expression in cultured theca cells maintained under serum-free conditions.The effect of thiomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
11
0
3
Order By: Relevance
“…Using well defined in vitro model systems based on primary cultures of bovine TC [26], [27], [28], [29] and GC [30], [31], [32], [33] the present study shows that VPA has a direct, dose-dependent inhibitory action on ovarian steroidogenesis, suppressing both basal and LH-induced androgen production by TC as well as FSH- and IGF-induced estrogen production by GC. With regard to TC, our findings concur with those of a recent study [22] documenting a VPA-induced inhibition of basal and hCG-induced androgen secretion by rat theca-interstitial cells.…”
Section: Discussionmentioning
confidence: 60%
“…Using well defined in vitro model systems based on primary cultures of bovine TC [26], [27], [28], [29] and GC [30], [31], [32], [33] the present study shows that VPA has a direct, dose-dependent inhibitory action on ovarian steroidogenesis, suppressing both basal and LH-induced androgen production by TC as well as FSH- and IGF-induced estrogen production by GC. With regard to TC, our findings concur with those of a recent study [22] documenting a VPA-induced inhibition of basal and hCG-induced androgen secretion by rat theca-interstitial cells.…”
Section: Discussionmentioning
confidence: 60%
“…This showed that ammonium tetrathiomolybdate can prevent induced differentiation of bovine granulosa cells cultured in vitro. A follow-up study showed that 5-100 µg/ml of ammonium tetrathiomolybdate can prevent induced differentiation of bovine theca cells in culture, but apparently not affect cellular morphology and cell number [Kendall et al 2006]. In addition, ammonium molybdate at 330 µg/ ml can inhibit cell division and differentiation in vitro [Kolesarova et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Zygotes were flushed from oviducts 18 h post-hCG injection, removed their cumulus cells by a brief exposure to 0.01% hyaluronidase, and then cultured in 50 µl droplets of potassium simplex optimized medium (KSOM) [Lawits and Biggers 1993] with 0,5,10,20,40,80,120, and 160 µg/ml of molybdenum (sodium molybdate dihydrate) covered under mineral oil at 377°C and 5% CO 2 in air for 5 d. The selection of those doses were based on previous reports [Kendall et al 2003;Kendall et al 2006;Kolesarova et al 2009] and the concentration that humans may be exposed [Huang et al 2011].…”
Section: Embryos and Treatmentmentioning
confidence: 99%
“…O cobre, magnésio e zinco regulam enzimas que participam da produção de progesterona (GOTTSCH; VAN KIRK;MURDOCH, 2000;KENDALL et al, 2006). A concentração de progesterona tem sido associada com a perda precoce embrionária (MANN;LAMMING, 2001;FORDE et al, 2011).…”
Section: Introductionunclassified
“…A concentração de progesterona tem sido associada com a perda precoce embrionária (MANN;LAMMING, 2001;FORDE et al, 2011). É necessário para formação de enzimas esteroidogênicas, tais como citocromo P450, 17 alfa-hidroxilase, citocromo P450 de clivagem de cadeia lateral e lisil oxidase, a presença do cobre (KENDALL et al, 2006). O zinco é um mineral que age nas enzimas endopeptidases e está envolvido na reorganização dos folículos ovarianos em um corpo lúteo eficiente, que são é responsável pela produção de progesterona, já o manganês atua como um co-fator para a síntese de colesterol, precursor da síntese de progesterona (OLSON, 1965).…”
Section: Introductionunclassified